Evaluation of Quality of Life: Functional Assessment of Chronic Illness Therapy after Thoracic Sympathectomy for Palmar Hyperhidrosis - Dobosz, Lukasz; Stefaniak, Tomasz (The Thoracic and Cardiovascular Surgeon, 2019)
Background Primary hyperhidrosis is a condition that significantly decreases the quality of life (QOL). Thoracic sympathectomy is safe and efficient method of treatment in palmar hyperhidrosis.Objective The aim of the study was to evaluate the change in QOL in patients with palmar hyperhidrosis who underwent thoracic sympathectomy.Methods The study includes 149 patients (37 men and 112 women) who were treated with bilateral thoracoscopic sympathectomy for primary palmar hyperhidrosis. Subjective and objective evaluation of hyperhidrosis were performed prior to the surgery, 3 and 12 months after the treatment. Control group consists of 305 healthy volunteers (118 men and 187 women). The QOL was measured using Functional Assessment of Chronic Illness Therapy (FACIT) scale.Results The average level of palmar hyperhidrosis in the study group prior to surgery was 224.69 ± 179.20 mg/min/m2. General QOL (FACIT total) before the surgery was significantly lower in the study group when compared with the control group (66.57 ± 16.33 vs. 91.29 ± 11.13; p < 0.05). Three months after surgery level of hyperhidrosis decreased significantly and remained at similar level 12 months after the procedure (13.55 ± 15.41 mg/min/m2p < 0.05 and 14.41 ± 18.19 mg/min/m2p < 0.05, respectively). After thoracoscopic sympathectomy, the QOL increased and did not differ when compared with the control group 3 and 12 months after the surgery (90.28 ± 11.13 vs. 91.29 ± 11.13; p = 0.55 and 89.59 ± 11.34 vs. 91.29 ± 11.13; p = 0.84, respectively). The highest increase was observed in functional well-being domain (32.25%); however, it was also noticeable in other domains.Conclusion Thoracic sympathectomy is an efficient method of treatment in palmar hyperhidrosis which significantly increases patients' QOL especially in a functional domain.
Keywords: palmar hyperhidrosis; quality of life; sympathectomy; gravimetry